1993
DOI: 10.1046/j.1365-313x.1993.04010125.x
|View full text |Cite
|
Sign up to set email alerts
|

BPF‐1, a pathogen‐induced DNA‐binding protein involved in the plant defense response

Abstract: The mechanisms by which plants restrict the growth of pathogens include transient activation of numerous defense-related genes. Box P is a putative cis-acting element of a distinct group of such genes, including those encoding the enzyme phenylalanine ammonialyase (PAL). A DNA-binding activity to Box P was identified in nuclear extracts from cultured parsley cells and a cDNA encoding the protein BPF-1 (Box P-binding Factor) partially characterized. BPF-1 binds to this element with specificity similar to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 0 publications
1
50
0
1
Order By: Relevance
“…Early promoter deletion studies have identified specific regions in the promoters of lignin biosynthetic genes responsible for wounding, UV irradiation and pathogen activations 51 and suggest that the AC elements are implicated in response to environmental stresses. 17,52 Further investigation on stress-specific cis elements and the corresponding transcription factors will be necessary to understand how stress signals are transduced to activate lignin biosynthesis. Finally, lignin constitutes 15-30% of the biomass of wood and understanding the transcriptional control of lignin biosynthesis during wood formation will have important implications in tree biotechnology.…”
Section: Discussionmentioning
confidence: 99%
“…Early promoter deletion studies have identified specific regions in the promoters of lignin biosynthetic genes responsible for wounding, UV irradiation and pathogen activations 51 and suggest that the AC elements are implicated in response to environmental stresses. 17,52 Further investigation on stress-specific cis elements and the corresponding transcription factors will be necessary to understand how stress signals are transduced to activate lignin biosynthesis. Finally, lignin constitutes 15-30% of the biomass of wood and understanding the transcriptional control of lignin biosynthesis during wood formation will have important implications in tree biotechnology.…”
Section: Discussionmentioning
confidence: 99%
“…1) with a Myb domain at the C-terminal region and with sequence similarity to a pathogen-induced DNA-binding protein (PcBPF-1). 24) We designated the gene encoding this protein as CTMyb1.…”
Section: Resultsmentioning
confidence: 99%
“…A parsley type II protein, PcBPF-1, interacts with box P of the PAL-1 promoter and might play a role in mechanisms of disease resistance by modulating plant defense gene expression. 24) A BPF-1-like protein from C. roseus has been found to interact with an elicitor-responsive region of a strictosidine synthase gene, Str. 25) However, there has been no direct evidence that the type II proteins regulate promoter activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its transcription levels are increased by heredity, plant hormones, pathogenic attack, tissue wounding, UV irradiation, low temperature, or low levels of nitrogen and phosphate (Xu, 2005;Cheng et al, 2009). CHS is an inducible gene, and its promoter region has a number of cis-acting elements associated with adversity, hormones, tissue specificity, and other systems with inducible expression apart from key regulatory elements, such as ACE elements, silencers, H-box sequences, and AT-rich units (Weisshaar et al, 1991;Yu et al, 1993;da Costa e Silva et al, 1993;Kiba et al, 1995). The CHS gene promoter sequence of Arabidopsis thaliana contains the UV-A/UV-B/blue ray response element, and its expression is strongly induced by blue and ultraviolet rays (Hartmann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%